PENATALAKSANAAN HOLISTIK PASIEN PRIA USIA 61 TAHUN DENGAN TB PARU, GIZI KURANG, MELALUI PENDEKATAN DOKTER KELUARGA DI WILAYAH PUSKESMAS GEDONG TATAAN - Joko Widodo Joko Widodo; Imelda Carolia (CV. Jasa Sukses Abadi, 2021)
Tuberculosis (TB) is still a problem in developing countries and even the world. TB is one of the top 10 causes of death and the first cause of death from an infectious agent worldwide. The government plans to eliminate TB by 2030, which is carried out with the National Strategy for TB control. Family doctors play an important role in which the role of family doctors is not only to cure but also to promote health and prevention of TB disease, Identifying risk factors, clinical problems, and providing management to patients with the application of holistic, evidence-based medicine-based family doctor services through a patient-centered approach and a family approach, The analysis of this study is case report. Primary data were obtained through history taking, physical examination and home visits to complete family data, psychosocial and environmental data. Secondary data were obtained from patient medical records at Puskesmas. Assessment is carried out based on a holistic diagnosis from the start, process, and end of the study quantitatively and qualitatively, The diagnosis of new cases of pulmonary TB with underweight in this patient is in accordance with national guidelines. The management given is in accordance with the guidelines, it can be seen that changes in behavior and knowledge of the patient and the patient's family are seen after intervention based on evidence-based medicine which is patient-centered, family approach.